2021
DOI: 10.3390/appliedchem1020012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Potential Pollutants from Poly(lactic acid) after the Degradation Process in Soil under Simulated Environmental Conditions

Abstract: In recent years, the amount of produced petrochemical plastic waste has been growing at an alarming rate. According to the Plastics Europe Market Research Group (PEMRG)/Conversio Market & Strategy GmbH, in 2018 the global production of plastics amounts to 359 million tons, and in Europe—61.8 million tons. More than 80% of all marine litter is plastic, which accumulates in the environment due to its durability. Due to the growing problem, biodegradable polymer products are introduced to the market. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The samples in the soil were in contact with water, oxygen, microorganisms, and PLA should decompose in lactic acid and then H 2 O, CO 2 , and nontoxic compounds. Nonetheless, it is considerably persistent in soil, which could be considered a pollutant material 77 . The addition of mango seed material would accelerate the degradation rate.…”
Section: Resultsmentioning
confidence: 99%
“…The samples in the soil were in contact with water, oxygen, microorganisms, and PLA should decompose in lactic acid and then H 2 O, CO 2 , and nontoxic compounds. Nonetheless, it is considerably persistent in soil, which could be considered a pollutant material 77 . The addition of mango seed material would accelerate the degradation rate.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of plastics depends on many factors, including properties of the polymer, chemical structure, molar mass, glass transition temperature, melting point, polydispersion, crystallinity, sample surface, etc. [98][99][100]. A study on the biodegradation of PLA showed that the higher the degree of crystallinity, the molar mass and the melting point, the slower is its degradation.…”
Section: Selected Research Methods Of the Biodegradation Processmentioning
confidence: 99%
“…A study on the biodegradation of PLA showed that the higher the degree of crystallinity, the molar mass and the melting point, the slower is its degradation. While in the first stage hydrolytic degradation can be observed, the second stage is related to the activity of microorganisms activity [98]. Liu et al [101] investigated biodegradation of PLA/PHB-blended nonwovens in the presence of microbial communities and indicated the role of Proteobacteria and Firmicutes in the process in a soil environment.…”
Section: Selected Research Methods Of the Biodegradation Processmentioning
confidence: 99%
“…Spectroscopic techniques such as FT-IR, UV-Vis, and Fluorescence, are mostly used to highlight variations in the building blocks of the polymer structure (Han 2016). Spectrometric approaches such as NMR and massspectrometry are widely used for the qualitative and quantitative determination of several classes of substances including low molecular weight pollutants, high molecular weight polymers up to supramolecular aggregates (Banerjee 2012;Indelicato 2016;Biale 2021;Krawczyk-Walach 2021) Therefore, all these analytical approaches can be very informative in synergy when it comes to evaluating a material undergoing various stresses or degradative processes (Kumar 2017;Akdoğan 2018;Falkenstain 2021;Ghasemlou 2022).…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%